Determinanan Kinerja Bisnis pada Sektor UMKM Halal: Studi Empiris Penggunaan Teknologi Digital dan Kapasitas Keuangan Pelaku Usaha dalam Perspektif Model CORTEX - Ika Farida Ulfah; Ardyan Firdausi Mustoffa; Wijianto Wijianto (Politeknik Ganesha Medan, 2026)
This study aims to analyze the influence of digital technology adoption and financial capacity on business performance in the Halal MSME sector in Ponorogo Regency from the perspective of the CORTEX model. The independent variables examined include e-commerce, digital payment, financial literacy, financial inclusion, and accounting knowledge. This research employs a quantitative approach using primary data collected through questionnaires distributed to Halal MSME owners. The population consists of 2,015 Halal MSMEs, with a sample of 89 respondents selected using the cluster sampling technique. Data were analyzed using multiple linear regression with SPSS 25 for Windows, supported by descriptive statistical analysis, data quality tests, classical assumption tests, and hypothesis testing. The results indicate that e-commerce, digital payment, financial literacy, financial inclusion, and accounting knowledge each have a significant partial effect on the performance of Halal MSMEs in Ponorogo Regency. This study contributes by extending the CORTEX model to the context of Halal MSMEs. The regression results indicate that digital adoption and financial capacity jointly explain 51.2% of the variation in business performance (R² = 0.512, p < 0.05). These findings highlight that optimizing digital technology utilization and strengthening the financial capacity of business actors are crucial factors in enhancing competitiveness and ensuring the sustainability of Halal MSMEs in the digital economy era.